Standards of care by multidisciplinary team for cleft lip and palate patients in Malaysia (A Pilot Study) / Umar Kamali - Umar, Kamali (2018)
Introduction: The management of cleft lip and palate (CLP) patients are complex and require coordinated care of multidisciplinary team (MDT). In Malaysia, cleft combined clinic (CCC) only available in small numbers and situated in urban centres. To date, there were limited number of research conducted to investigate standard of care for CLP patients among CCC in Malaysia. Objective: The aims of this study is to investigate the standards of care provided for management of cleft lip and palate (CLP) patients in Malaysia in comparison to the recommendations made by Clinical Standards Advisory Group (CSAG) UK 1998. Methods: This is a cross sectional questionnaire-based survey study. The self-administered postal questionnaire comprises of few components that was related to the cleft team services which include overall cleft services, team formation, team members, clinical sessions & infrastructure and audit practice. Results: All questionnaires were send to three university hospitals which provide cleft services. It was found that the composition of each cleft team varies through the MDT model in every centre. Oral & maxillofacial surgeon (OMFS) and orthodontist were the only specialties that attended most of the time in CCC in all cleft teams. All centres provided complete treatment for cleft patients starting from baby until adulthood. There was variation in surgeons that involved in primary lip and palate repair while alveolar bone graft (ABG) surgery was done mainly by OMFS. None of the cleft team used database for their record keeping and actively involved in clinical audit program. Conclusions: Management for CLP patients among university hospital in Malaysia was provided through a MDT model care as recommended by CSAG UK 1998 with some of the recommendations fulfilled by the cleft team. However, improvement are needed especially in the area of forming a database for record keeping and having a routine clinical audit program. KEYWORDS: Cleft lip and palate, Clinical Standards Advisory Group, Multidisciplinary team